2012
DOI: 10.1117/1.jbo.17.6.066019
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of near-infrared functional lymphatic imaging

Abstract: Abstract. Near-infrared imaging of lymphatic drainage of injected indocyanine green (ICG) has emerged as a new technology for clinical imaging of lymphatic architecture and quantification of vessel function, yet the imaging capabilities of this approach have yet to be quantitatively characterized. We seek to quantify its capabilities as a diagnostic tool for lymphatic disease. Imaging is performed in a tissue phantom for sensitivity analysis and in hairless rats for in vivo testing. To demonstrate the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 43 publications
6
75
0
Order By: Relevance
“…Recent innovations to study pump function of lymphatic vessels isolated from mice opens the door to a wide variety of transgenic and knockout models to expand our knowledge (Liao et al, 2011; Scallan and Davis, 2013). New techniques to non-invasively study lymphatic function in both animals and humans are also emerging and will aid with understanding human lymphedema (Aldrich et al, 2012; Maus et al, 2012; Nelson et al, 2014; Rasmussen et al, 2010; Tan et al, 2011; Weiler and Dixon, 2013; Weiler et al, 2012). These new approaches will help with the continued need to investigate the cellular and molecular mechanisms by which lymphatic vessels respond to mechanical cues to optimize lymph flow.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Recent innovations to study pump function of lymphatic vessels isolated from mice opens the door to a wide variety of transgenic and knockout models to expand our knowledge (Liao et al, 2011; Scallan and Davis, 2013). New techniques to non-invasively study lymphatic function in both animals and humans are also emerging and will aid with understanding human lymphedema (Aldrich et al, 2012; Maus et al, 2012; Nelson et al, 2014; Rasmussen et al, 2010; Tan et al, 2011; Weiler and Dixon, 2013; Weiler et al, 2012). These new approaches will help with the continued need to investigate the cellular and molecular mechanisms by which lymphatic vessels respond to mechanical cues to optimize lymph flow.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Although it is fairly well established that long-chain fatty acids are almost exclusively transported in lymph in the intestine even in the presence of blood capillaries, since the size of the molecules are too large to significantly penetrate the blood endothelial barrier (40). Indeed, near-infrared imaging data from our lab in other tissue beds has demonstrated that particles larger than a few nanometers are preferentially taken up by the lymphatics, not the vasculature (41,42). In vivo the presence of flow in the lacteal through open junctions would produce a convective force that favors paracellular transport.…”
Section: Discussionmentioning
confidence: 97%
“…Photons near the infrared range of the spectrum penetrate farther than those near the ultraviolet. Thus, with optics and detectors that operate in the near infrared, it is possible to obtain relatively high resolution images up to a few millimeters into soft tissues (Weiler et al, 2012). This requires fluorescent tracers that absorb and emit at near infrared wavelengths, generally in the 750–1000 nm range.…”
Section: Imaging the Lymphatic System In The Clinic For Assessment Ofmentioning
confidence: 99%